Tinjauan Yuridis Atas Pajak Daerah dan Retribusi Daerah Dikaitkan Dengan Pelaksanaan Otonomi Daerah - Kadarukmi, M.E. Retno (Jurnal Administrasi Bisnis, 2010)
With the enactment of the Law on Local Government which regulates the delegationof authority and responsibility the Central Government to Local Governments, andthe emergence of the Law on Financial Balance between Central and Local Governments,are appropriately regions can develop local resources and reduce on theLocal to the Central Government. but, from a variety of empirical observations showthat the implementation of regional autonomy has led to distortions and high costeconomy.In this paper will try to describe and explain the fact that there are policies thatcan be taken to improve the financial performance of Local Government in order toachieve improvement of regional real income to finance sustainable development.Keywords: Local government, central government, autonomy, regional real income,regional tax